2019
DOI: 10.1103/physrevapplied.12.034005
|View full text |Cite
|
Sign up to set email alerts
|

Nonvolatile Ionic Modification of the Dzyaloshinskii-Moriya Interaction

Abstract: The possibility to tune the Dzyaloshinskii Moriya interaction (DMI) by electric (E) field gating in ultra-thin magnetic materials has opened new perspectives in terms of controlling the stabilization of chiral spin structures. Most recent efforts have used voltage-induced charge redistribution at the interface between a metal and an oxide to modulate DMI. This approach is attractive for active devices but it tends to be volatile, making it energy demanding, and it is limited by Coulomb screening in the metal. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 45 publications
0
56
0
Order By: Relevance
“…This is consistent with previous reports in the literature where the effect of interface roughness and intermixing on the inversion symmetry breaking has been extensively studied. It was reported that the DMI and the domain wall velocity increased with the difference of roughness and intermixing between the top and bottom interface of a magnetic layer 39,40,44,45 . Finally, as the skyrmion size depends on the magnetic film thickness 22,34 , it is thus important to understand how the interfacial DMI scales with the thickness.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with previous reports in the literature where the effect of interface roughness and intermixing on the inversion symmetry breaking has been extensively studied. It was reported that the DMI and the domain wall velocity increased with the difference of roughness and intermixing between the top and bottom interface of a magnetic layer 39,40,44,45 . Finally, as the skyrmion size depends on the magnetic film thickness 22,34 , it is thus important to understand how the interfacial DMI scales with the thickness.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to electric-field gating, electric-field-induced strains in the ferroelectric can be transferred to the FM layer over hundreds of nanometers 26 or more, which should lead to a more effective skyrmion manipulation by modulating both the magnetic anisotropy and the interfacial DMI of the HM/FM interface. Notably, electric-field control of the interfacial DMI of the HM/FM interface has so far only been observed through ionic-liquid-gating-induced carrier density change 27 , and the ionic-liquid may damage the sample. Instead, a nondestructive HM/FM interfacial DMI modulation could be achieved via the strain-mediated electric-field control in all-solid-state heterostructures/devices.…”
Section: Introductionmentioning
confidence: 99%
“…[3,12,14,19,20] To date, studies on magnetoionic effects in thin metal films have focused primarily on changes in the interfaceperpendicular magnetic anisotropy (PMA) [21][22][23][24][25] and the Dzyaloshinskii-Moriya interaction. [26] There is growing recognition that voltageinduced changes in valency and phase, inherent to magnetoionic effects, can be applied to the magnetic layer beyond the interface. [13,17] For instance, voltagecontrol of magnetization up to ON/OFF switching of magnetism is possible in transition metal oxide (TMO) [13,27] and hybrid TMO/metal films [28][29][30] because of the switching between different chemical states induced by oxygen, hydrogen, or lithiumion transport.…”
Section: Introductionmentioning
confidence: 99%
“…Since the magnetization processes rely on the evolution of magnetic domains, the local magnetic microstructure is a decisive tool for understanding magneto ionic effects. Until now, the modulation of domain expan sion, [12,26] domain contrast, [25] and domain size [40] after ionic modification of thin films have been reported. However, there have been no reports of the direct and simultaneous detection of electrochemical oxidation/reduction reactions and changes in the magnetic domain structure.…”
Section: Introductionmentioning
confidence: 99%